2017
DOI: 10.1161/jaha.116.004746
|View full text |Cite
|
Sign up to set email alerts
|

Rac1 Pharmacological Inhibition Rescues Human Endothelial Dysfunction

Abstract: BackgroundEndothelial dysfunction contributes significantly to the development of vascular diseases. However, a therapy able to reduce this derangement still needs to be identified. We evaluated the effects of pharmacological inhibition of Rac1, a small GTPase protein promoting oxidative stress, in human endothelial dysfunction.Methods and ResultsWe performed vascular reactivity studies to test the effects of NSC23766, a Rac1 inhibitor, on endothelium‐dependent vasorelaxation of saphenous vein segments collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Although previous studies have suggested a reduction in eNOS expression after Rac1 inhibition,36 the modulation of Rac1 activity by NSC23766 in our study was not related to changes in its expression in both mouse vessels and human endothelial cells. Moreover, we were recently able to demonstrate that Rac1 inhibition by NSC23766 exerts a beneficial effect also in human vessels, ameliorating endothelial dysfunction 16. These results pointed out the important role of Rac1 as a therapeutic target to improve vascular homeostasis.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Although previous studies have suggested a reduction in eNOS expression after Rac1 inhibition,36 the modulation of Rac1 activity by NSC23766 in our study was not related to changes in its expression in both mouse vessels and human endothelial cells. Moreover, we were recently able to demonstrate that Rac1 inhibition by NSC23766 exerts a beneficial effect also in human vessels, ameliorating endothelial dysfunction 16. These results pointed out the important role of Rac1 as a therapeutic target to improve vascular homeostasis.…”
Section: Discussionmentioning
confidence: 75%
“…Moreover, we were recently able to demonstrate that Rac1 inhibition by NSC23766 exerts a beneficial effect also in human vessels, ameliorating endothelial dysfunction. 16 These results pointed out the important role of Rac1 as a therapeutic target to improve vascular homeostasis. Levay et al 27 have demonstrated an effect of NSC23766 as nonselective competitive antagonist of muscarinic acetylcholine receptors in neonatal rat cardiomyocytes.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…2 Hypoxia-induced CMECs injury is considered as an initiating process and pathological basis of various cardiovascular diseases, 3 and protecting CMECs from hypoxia insult might thus be an important therapeutic strategy for treating various cardiovascular diseases. 4 Hypoxia can insult various endothelial cell biological activities such as cell growth, survival, migration and energy metabolism, which may lead to angiogenesis impairment, redundant reactive oxygen species (ROS) generation, mitochondrial dysfunction and energy metabolism disturbance to some extent.…”
mentioning
confidence: 99%